First Production of Magnesium Metal from the Sea! - Dow Chemical Company (1941)
Color print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. The advertisement features waves moving across the sea, with accompanying text commemorating Dow's production of magnesium metal extracted from seawater on January 21, 1941. The advertisement also details Dow's efforts to ramp up production to meet increased wartime demand, specifically the production of aircraft.
Keywords: Dow Chemical Company; Chemical industry; Corporations; Advertising; Advertising, Industrial; Magnesium; Magnesium alloys; Magnesium industry and trade; Seawater